RETRACTED ARTICLE: Association between cytochrome P450 1A1 (CYP1A1) gene polymorphisms and the risk of renal cell carcinoma: a meta-analysis - Fan-dong Meng; Ping Ma; Cheng-guang Sui; Xin Tian; You-hong Jiang (Scientific Reports)
Abstract Cytochrome P450 1A1 (CYP1A1) usually metabolizes carcinogens to their inactive derivatives but occasionally converts the chemicals to more potent carcinogens. To date, many studies have evaluated the association between the CYP1A1 MspI and Ile462Val polymorphisms and renal cell carcinoma (RCC) risk, but the results have been conflicting. To more precisely evaluate the potential association, we carried out a meta-analysis of seven published case-control studies. The meta-analysis indicated that the MspI polymorphism was associated with an increased RCC risk (allele model: OR = 1.49, 95%CI 1.03–2.16; homozygous model: OR = 1.64, 95%CI 1.13–2.40; dominant model: OR = 1.72, 95%CI 1.07–2.76). No significant associations were found for the Ile462Val polymorphism for all genetic models. When stratified by smoking status, smokers carrying the variant Vt and Val allele were more susceptible to RCC (Vt allele: OR = 3.37, 95%CI = 2.24–5.06; Val allele: OR = 2.07, 95%CI = 1.34–3.19). These data indicate that the CYP1A1 MspI polymorphism significantly increased RCC risk, while the Ile462Val polymorphism was not associated with RCC. Among smokers, individuals with the CYP1A1 Vt allele and Val allele showed a significantly increased risk of RCC. More well-designed studies with larger samples are warranted to show the underlying mechanisms of CYP1A1 in the development of RCC.